Neurotransmitters and molecular chaperones interactions in cerebral malaria: Is there a missing link? - Daniyan, Michael Oluwatoyin; Fisusi, Funmilola Adesodun; Adeoye, Olufunso Bayo (Frontiers in Molecular Biosciences, 2022)
Plasmodium falciparum is responsible for the most severe and deadliest human malaria infection. The most serious complication of this infection is cerebral malaria. Among the proposed hypotheses that seek to explain the manifestation of the neurological syndrome in cerebral malaria is the vascular occlusion/sequestration/mechanic hypothesis, the cytokine storm or inflammatory theory, or a combination of both. Unfortunately, despite the increasing volume of scientific information on cerebral malaria, our understanding of its pathophysiologic mechanism(s) is still very limited. In a bid to maintain its survival and development, P. falciparum exports a large number of proteins into the cytosol of the infected host red blood cell. Prominent among these are the P. falciparum erythrocytes membrane protein 1 (PfEMP1), P. falciparum histidine-rich protein II (PfHRP2), and P. falciparum heat shock proteins 70-x (PfHsp70-x). Functional activities and interaction of these proteins with one another and with recruited host resident proteins are critical factors in the pathology of malaria in general and cerebral malaria in particular. Furthermore, several neurological impairments, including cognitive, behavioural, and motor dysfunctions, are known to be associated with cerebral malaria. Also, the available evidence has implicated glutamate and glutamatergic pathways, coupled with a resultant alteration in serotonin, dopamine, norepinephrine, and histamine production. While seeking to improve our understanding of the pathophysiology of cerebral malaria, this article seeks to explore the possible links between host/parasite chaperones, and neurotransmitters, in relation to other molecular players in the pathology of cerebral malaria, to explore such links in antimalarial drug discovery.